Simulation of Calcite Calcination - A. G. Kоzhevnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Mathematical modeling and experimental investigation results of heat transfer in the case of calcite calcinations in regenerative shaft furnaces are given in the paper. Influence of heating gas temperature, calcined material fragment size and desired final product output on the duration of calcite calcination has been studied. It has been shown that with the given percentage of final product output and permissible changes in heating gas temperature in the furnace it is the fraction size of the calcined material that greatly determines such parameter as a process duration.